ANALISIS KASUS SEDIMENTASI DI TIGA TITIK KAWASAN WATER FRONT CITY - Yuda Romdania (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
Prediction of sediment transport along the coast for various conditions is very important to knowin order to know the amount of sediment transport and examine the influences that tend toprovoke. Existence of the buildings on the coast will cause sedimentation in one hand and on theother side causing erosion. Bandar Lampung is city with a coastal region, is currently designing ajob that is Water Front City (beach city) which is designed in an effort to carry out vision andmission of Bandar Lampung City which is "Making the city of Bandar Lampung become civilized,comfortable and sustainable." The existence of this work it is necessary to design a sedimentationanalysis in order to know the amount of the resulting sediment transport and the influences whichtend to be caused due to designing Water Front City. Data collection is performed at three pointsthen inserted to CERC Equation which get a conclusion of sediment movement from two pointsconical at one point which is toward the Panjang Port, resulting a large pile of sediment aroundPanjang Port area.